Design, Construction and Simulation of Tesla Turbine - SMG Akele; M. Ejededawe; G. A.Udoekong; A. Uwadiae; M. E. Oviawe; B. O. Ayewa (International Journal of Engineering and Management Research, 2021)
Investigations of laminar fluid flow between two moving or stationary plates, and two rotating discs, over the years were geared toward how to increase Tesla-based turbine efficiency. Therefore, this research entails the construction, design and simulation of a Tesla turbine in order to investigate the potential of Tesla turbine for energy generation. Method of solution entails the design and construction of a physical model Tesla turbine from locally sourced materials. The physical model geometry and design parameters were then used to conduct numerical simulation. Performance evaluation was then carried on the physical model and the simulation model. The result showed that voltage, current and power all increase with increase in rev. per minute. The result obtained indicates that for higher power generation, a Tesla turbine design with higher revolution per minute capability will be required. Turbine model simulation showed that radial velocity vector to be concentrated at the discs periphery and outlet. The research results are good references for design of larger Tesla turbine for community use.